The impact of institutions for multinationals entering emerging markets, an Amazon case study - Ziliotto, Bruno Martimbianco (2022)
Classic international business theories such as industry-based view and resource-based view have contributed to explaining companies’ decisions during decades. Still, Peng noticed some aspects that impacted those companies which previous theories have missed. Bringing to light the institutional-based view, the author complemented the two previous approaches, creating the strategy tripod and adding more context to the international business analysis environment. The main goal of this dissertation is to analyze the entering process of Amazon into the Brazilian market, using the strategy tripod, focusing on the institutional-based view, seeking to understand how institutions impacted the company's decisions during the process. Using extensive data research and interviews, the author aims to study the influence of local institutions, such as regulators, competitors, and customer habits. After extensively analyzing those three factors, the main findings were (1) tax and legal regulations are so complex that need to be considered into the companies’ strategy; (2) competition is fierce in the Brazilian market and companies use high levels of investment and innovation to set them apart; (3) Amazon seems to be understanding the local costumers after a few years of adaptations to their way of doing business. Finally, the study aimed to add knowledge to the international business literature regarding emerging markets, especially Brazil, and to confirm the importance of the institutional-based view, complementing the strategy tripod when analyzing a company.